Friedelin induces apoptosis in oral cancer: Insights from in vitro and in silico studies - Ramya Sekar; Monisha Prasad; Manikandan Alagumuthu (Journal of Oral Biology and Craniofacial Research)
Background: Oral cancer is a major health issue in the world because of its high morbidity and mortality rates. Dysregulated apoptosis, is involved in tumor progression and treatment resistance. Friedelin, a natural triterpenoid, has been shown to have potential to modulate apoptosis pathways. This study investigates the therapeutic effects of Friedelin, particularly on its interactions with apoptotic proteins, cytotoxic effects on KB oral cancer cells, and ability to induce apoptosis through intrinsic signaling pathways. Materials and methods: Interaction networks were constructed by taking target genes related to Friedelin and oral cancer identified by CTD and GeneCards, and applying them in the STITCH database for analysis. Apoptotic binding affinity of key proteins, towards Friedelin was determined using molecular docking. The cytotoxic potential of Friedelin was accessed by performing in vitro assays such as MTT, morphology analysis, and Annexin V-FITC flow cytometry. The regulation of Friedelin on apoptosis was validated through gene expression analysis. Results: Network analysis identified Friedelin's critical interactions with apoptotic regulators. Molecular docking revealed strong binding affinities, particularly with Bax (−8.3 kcal/mol) and Bcl2 (−8.0 kcal/mol). Cytotoxicity assays showed dose- and time-dependent effects. Gene expression analysis confirmed upregulation of Bax, Caspase-3, and TP53, and downregulation of Bcl2, demonstrating activation of intrinsic apoptotic pathways. Conclusion: Friedelin is an anticancer agent that has great potential for oral cancer treatment by modulating apoptotic signaling pathways and inducing apoptosis. Future studies should be conducted on the in vivo validation and clinical translation of Friedelin as a novel therapeutic candidate.